OneNote 2016 : a complete guide - McCrae, Ed; Safari eBooks ([Place of publication not identified] : Intellezy, 2018)
"This course is an introduction to, and in-depth look at the OneNote 2016 program. During the course, students will learn how OneNote can help them to organize their notes more efficiently, and allow them to access their content from anywhere. Students will also learn how to share the contents of their OneNote notebooks with others, and collaborate."--Resource description page.
Presenter, Ed McCrae.
Title from resource description page (Safari, viewed March 6, 2018).
Keywords: Microsoft OneNote; Note-taking -- Computer programs; Personal information management -- Computer programs; Electronic books